Review of causes of stillbirths in a rural referral hospital: a cross sectional study - Asalkar, Mahesh R.; Surve, Meenakshi; Dhakne, Swapnil R.; Shivamurthy, H. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The birth of a newborn after twenty-eight completed weeks of gestation weighing 1,000 gm or more, with baby showing no signs of life after delivery is a still born’’. Such death includes both antepartum and intrapartum death. Stillbirths (SB) are the largest contributor to perinatal mortality. Of the estimated 3 million stillbirths which occur yearly, the vast majority are in developing countries, with rates in many developing countries ten-fold higher than elsewhere. Methods: Descriptive (cross sectional) study was conducted at tertiary referral hospital in rural area of Maharashtra from September 2015 to August 2017. Out of total 3235 deliveries during study period 64 mothers giving birth to 66 cases of still birth (2 cases of twins) satisfied the inclusion criteria and studied to find out prevalence, causes and high-risk factor association with stillbirth. Results: Stillbirth rate in our study was 20.4/1000 deliveries. 56.25% patients were in the 21-25 years age group.9.3% were illiterate while 57.81% had education below 12th standard. Most patients were from low socioeconomic status and 57.81% were unregistered. Stillbirth was more common in Para (2-4), premature baby and with male sex preponderance in our study. Most patients 90.62% were delivered vaginally. Preeclmpsia, Abruption, Anaemia were common high-risk factor associated with stillbirth.54.6% cases were unexplained stillbirth while IUGR was noted in 23.4% cases and other causes noted were prematurity, congenital anomaly, cord and placental causes were found in our study. Conclusions: A significant proportion of stillbirths are preventable by adequate antenatal care. Female literacy and health education, adequate antenatal care, identification of high-risk cases, and timely referral needs to be emphasized among the medical and paramedical personnel at the first point of contact with the pregnant women.